Efisiensi Penurunan Parameter BOD, TSS, Minyak dan Lemak pada Limbah Greywater dengan Ecotech Garden Menggunakan Tanaman Melati Air (Echinodorus Palaefolius) - Irawan, Bambang; Hamzah, A. Hadian Pratama; Nurmawati, Subekti (Universitas Batanghari Jambi, 2024)
This study aims to analyze the efficiency of reducing BOD, TSS, oil and fat parameters in graywater waste, explaining the optimal residence time and percentage of plant cover needed in graywater waste treatment, designing a graywater waste treatment design model with Ecotech Garden using water jasmine plants (Echinodorus palaefolius) on a household scale. This research was conducted using a Randomized Complete Block Design conducted as many as 3 (three) replications. Factor 1 (treatment) measured is the residence time of 0.5 days, 1 day, 2 days, 3 days and factor 2 (group) is the percentage of plant cover which is 0%, 40%, and 80 Based on the research that has been done, the results show that the efficiency of reducing BOD levels ranges from 74.92% to 81.40%, TSS ranges from 96.02% to 97.59%, oil and fat ranges from 94.35% to 97.36%. The optimum residence time and percentage of plant cover is a residence time of 1 day in the reactor basin with a plant cover percentage of 40% with a BOD reduction efficiency of 81.40%. The Ecotech Garden design with a residence time of 1 day obtained dimensions of length 1.6 m width 1 m depth 0.70 m with a percentage of cover 40% obtained the number of water jasmine plants (Echinodorus palaefolius) as many as 15 plants so that this design can be applied in the home yard.